Cross-Cultural Ageism: Perspectives from Nursing Students in the USA and Japan - Therese Doan; Sumiyo Brennan; Jongmi Seo; Hisao Osada; Michiyo Bando (Journal of Ageing and Longevity)
Age discrimination in nursing may result in judgmental care and compromise the quality of care offered to older adults. While geriatric–gerontological education can address ageism among nursing students, cross-cultural perspectives on aging remain understudied. This study describes the characteristics of nursing students in the USA and Japan and explores their perspectives on aging after completing a life review assignment, both personally and professionally. A mixed-methods study using quantitative surveys and an exploratory–descriptive qualitative design was conducted at two nursing schools (one each in the USA and Japan). Students participated voluntarily with strict anonymity and confidentiality. There were significant differences between American and Japanese nursing students in both demographics and perceived impact of the life review assignment. The American students were predominantly older and had more experience in caregiving for older adults, whereas the Japanese students were younger and lacked such experience. The qualitative analysis revealed an increased awareness of patient-centered care for older adults as a major professional theme across both groups. The life review assignment proved effective in providing meaningful experiential learning opportunities for future nurses across different cultural contexts. This method appears promising in addressing ageism through personalized engagement with older adults.